2021
DOI: 10.1177/03611981211055664
|View full text |Cite
|
Sign up to set email alerts
|

If We Build It, Who Will Come? Comparing Sociodemographic Characteristics of Bike Share Subscribers, Cyclists, and Residents of New York City

Abstract: Bike share programs are becoming increasingly popular across U.S. cities. However, their impact on persistent disparities in cycling by gender, race, and socioeconomic status remains understudied. We examined whether subscribers of Citi Bike, New York City’s (NYC) largest bike share program, reflect the sociodemographic profile of NYC cyclists. Using NYC Community Health Survey data, we described adult NYC residents of neighborhoods with ≥1 Citi Bike stations who rode a bicycle at least once a month. Citi Bike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The same study found that bikeshare initiatives were not reaching segments of the population who were not already prone to cycling in New York City ( 65 ). Another study by Gehrke et al ( 66 ) stated that neighborhoods with a larger proportion of renter-occupied dwellings and historically disadvantaged populations have less access to dockless bikes while simultaneously having higher bike utilization rates.…”
Section: Review Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The same study found that bikeshare initiatives were not reaching segments of the population who were not already prone to cycling in New York City ( 65 ). Another study by Gehrke et al ( 66 ) stated that neighborhoods with a larger proportion of renter-occupied dwellings and historically disadvantaged populations have less access to dockless bikes while simultaneously having higher bike utilization rates.…”
Section: Review Methodologymentioning
confidence: 99%
“…Similarly, Qian and Jaller ( 64 ) used a dataset from Divvy bikeshare in Chicago, and the results indicated that bikeshare journeys are more likely to occur in areas with increased accessibility (i.e., the ability to use various mobility services and technologies, the ability to reach significant destinations/opportunities, or both). CitiBike in New York City is one of the largest bikeshare programs in the U.S. ( 65 ).…”
Section: Review Methodologymentioning
confidence: 99%